TINJAUAN YURIDIS PERNIKAHAN SIRRI DALAM PANDANGAN MUHAMMADIYAH DAN HUKUM POSITIF INDONESIA - Imawanto Imawanto; Edi Yanto; Fahrurrozi Fahrurrozi; Hamdi Hamdi; Yulias Erwin; Sahrul Sahrul (Universitas Muhammadiyah Mataram, 2021)
There are still many unregistered marriages (sirri) and only based on religion, while on the other hand Indonesia is not a religious state. When there are citizens who do unregistered marriages, of course the parties who are greatly disadvantaged are the women who are the wives of sirri, and their children. Their rights cannot be accommodated by State legal instruments, because their marriage is not recorded in the State register. This research focuses on problems related to unregistered marriages in the view of Muhammadiyah and Indonesian positive law and the consequences of unregistered marriages for the parties, especially wives, children and assets obtained from unregistered marriages, from the perspective of Indonesian positive law. The method used is a normative juridical research with a statutory approach and a conceptual approach. The results of the research are First, that the Muhammadiyah organization through its Tarjih Council and Tajdid supports or agrees with the Unitary State of the Republic of Indonesia. Every marriage of the nation's children must be carried out in front of an authorized official. Second, the positive law of the Indonesian state requires that every marriage must be registered in the state register, in order to obtain legal certainty. Third, the consequences of a sirri marriage carried out by the parties in this case the husband and wife will harm the wife and children born from the marriage, because they do not have legal certainty in demanding their civil rights.Keywords: Unregulated Marriage; Muhammadiyah; Indonesian Positive Law. ABSTRAKMasih maraknya pernikahan di bawah tangan atau pernikahan sirri yang berbasis agama saja, sementara disisi lain Indonesia bukan negara agama. Ketika warga Negara ada yang melakukan pernikahan sirri tentu pihak yang sangat dirugikan adalah perempuan yang menjadi istri sirri, dan anak-anaknya. Hak mereka tidak bisa diakomodasi oleh perangkat hukum Negara, karena pernikahanya tidak di catatkan di dalam register Negara. Penelitian ini pada permasalahan terkait pernikahan sirri dalam pandangan Muhammadiyah dan hukum positif Indonesia dan konsekuensi pernikahan sirri tersebut bagi para pihak, khususnya istri, anak dan harta kekayaan yang di peroleh dari pernikahan sirri, perspektif hukum positif Indonesia. Metode yang digunakan adalah penelitian yuridis normatif dengan pendekatan peraturan perundang-undangan (statute approach) dan pendekatan konseptual (conceptual approach). Hasil penelitiannya adalah Pertama, bahwa organisasi Muhammadiyah lewat Majelis Tarjih dan Tajdid-nya mendukung atau sepakat dengan Negara Kesatuan Republik Indonesia. Setiap pernikahan anak bangsa harus dilakukan dihadapan pejabat yang berwenang. Kedua, hukum positif negara Indonesia mewajibkan bahwa setiap pernikahan harus di catatkan diregister negara, agar mendapatkan kepastian hukum. Ketiga, Akibat dari pernikahan sirri yang dilakukan oleh para pihak dalam hal ini suami dan istri akan merugikan pihak istri dan anak-anak yang dilahirkan dari pernikahan tersebut, karena tidak mempunyai kepastian hukum dalam menuntut hak-hak keperdataannya.